2017
DOI: 10.1021/acs.macromol.7b00422
|View full text |Cite
|
Sign up to set email alerts
|

Donor–Node–Acceptor Polymer with Excellent n-Doped State for High-Performance Ambipolar Flexible Supercapacitors

Abstract: A redox active polymer network film containing donor–node–acceptor (D–n–A) units was prepared by using the electropolymerization (EP) of the precursor (4Cz–4Cl–PBI). The polymer film was characterized by the UV–vis absorption, FT-IR, SEM, XRD and electrochemical techniques. The precursor contains phenyl connected two carbazoles (D) linked by the two sp3 N-nodes on both sides of a tetrachloro-substituted PBI (A). The two N-nodes block the conjugation between D and A units, resulting in an independent redox acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…These characteristic peaks confirm the co-existence of carbonyl groups and two types of C-N bonds in APCNDI. The 13 C NMR spectrum shows characteristic chemical shifts at 162 and 141 ppm corresponding to the C atoms in the carbonyl groups of NTCDI and in the C-N bonds of the carbazole groups [39]. The absorption peaks in the UV-vis spectra are consistent with the results reported in the Ref.…”
Section: Articlessupporting
confidence: 88%
See 1 more Smart Citation
“…These characteristic peaks confirm the co-existence of carbonyl groups and two types of C-N bonds in APCNDI. The 13 C NMR spectrum shows characteristic chemical shifts at 162 and 141 ppm corresponding to the C atoms in the carbonyl groups of NTCDI and in the C-N bonds of the carbazole groups [39]. The absorption peaks in the UV-vis spectra are consistent with the results reported in the Ref.…”
Section: Articlessupporting
confidence: 88%
“…3d). A peak at 745 cm −1 was observed in the FTIR spectra of the pristine and low-voltage-cycled cathodes, which corresponds to the out-of-plane -C-H bending vibration of bis-substituted benzene [39]. Nevertheless, it is absent for the high-voltage cycled cathodes, showing that the benzene rings in the carbazole groups varied from bis-substituted to tri-substituted, confirming the occurrence of electropolymerization at high voltages.…”
Section: Articlesmentioning
confidence: 78%
“…c) Comparison of ambipolar polymer cycling stability in positive (black) and negative (red) regions. 24,27 result of the interaction of densely packed PDI units in reduced states with cations. 42 In the negative region, the x-axis of the Nyquist plot shifts to more positive values, suggesting increased resistance relative to the positive and neutral potentials.…”
Section: Resultsmentioning
confidence: 99%
“…Qin et al synthesized a donor-nodeacceptor polymer, consisting of a dicarbazole donor unit and a tetrachlorinated perylene diimide (PDI) acceptor unit. 27 This donor-node-acceptor architecture decouples the performance of the positive and negative charge storage by separating the negative charge accepting PDI unit from the positive charge accepting dicarbazole through the node-like nitrogen atoms. 28 Contrary to most ambipolar polymers, the donor-nodeacceptor network polymer synthesized by Qin et al demonstrated remarkable negative region stability of 89% capacity retention after 1000 cycles, but limited positive region stability.…”
Section: Introductionmentioning
confidence: 99%
“…This decreases the experimental time and cost and partially solves the solubility problem of some compounds. A large number of electropolymerized films have been prepared from monomers functionalized with thiophene or carbazole derivatives [22,23,24,25,26,27,28]. In addition, triphenylamine groups have been used as polymerizable units to prepare thin films of organic and metal complexes by electropolymerization [29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%